An abnormal meta-stable nanoscale eutectic reaction revealed by in-situ observations. (1st February 2019) - Zhou, Lin; Meng, Fanqiang; Zhou, Shihuai; Sun, Kewei; Kim, TaeHoon; Ott, Ryan; Napolitano, Ralph; Kramer, Matthew J.
Abstract: Phase selection and growth of materials far from equilibrium provides fertile ground for novel phases and morphologies since a multitude of different pathways may be energetically accessible. In this study, a complex metastable devitrification of Al60 Sm11 (ε-phase) from its amorphous precursor is discovered using a combination of in-situ high-energy X-ray diffraction (HEXRD), providing insight into the average bulk behavior, and in-situ aberration corrected scanning transmission electron microscopy, revealing the atomic scale mechanisms of growth and their dynamics. We have found that non-equilibrium chemical partitioning disrupts the nominal planer growth by formation of nanoscale Al enriched regions inhomogeneously segregated at the ε/glass interface, to locally balance the compositionally dependent driving force and the associated diffusional burden imposed on its grain growth. These Al-rich regions form fcc -Al-rich nanocrystallites epitaxially with the ε-phase, modifying ε/glass interface mobility and creating a crenulated growth front. This new mechanism offers a pathway for fabricating alloy structures with nanoprecipitate dispersions through a meta-stable phase transition. Graphical abstract: Image 1